Improvement of Pineapple Production on Tropical Peat Through Fertilizer Use - A. H. M., Razzaque (1999)
Information on the agronomic characteristics and nutritional requirements of pineapple (cv. Gandul) is lacking in peat soil. Therefore, studies in the field at two sites (site 1 and site 2), glasshouse and laboratory were carried out to investigate the effects of N, P, K, Ca, Mg and Cu on growth, yield and quality of pineapple and to assess the loss of the applied nutrients through leaching. Six levels of each of N, P, K, Ca, Mg and Cu were studied separately at each site of the field in a RCB design with three replications. In the glasshouse, three levels of each of the above nutrients were studied with soils from both sites. Leaching studies using soil columns were conducted in the laboratory with two levels of each nutrient for a period of 3 0 days. Plant height and leaf number increased with age up to forcing time at both sites. D-leaf length and area were influenced with N application, while the leaf dry weight was influenced with Mg at site 2 . The leaf nutrient concentrations were influenced by N, P, Ca and Mg at site 1 and by N, P and K applications at site 2. Leaf nutrient concentrations increased up to six months of plant age and declined at forcing at both sites. The mean fruit weight of pineapple responded quadratically with N application at both sites and with Ca at site 1 and declined linearly with the increment of P at site 2. There was no significant effect of nutrients on fruit quality except for P on sugar content at site 1 . Fruit yield was positively correlated with leaf N concentrations at both sites and negatively correlated with Cu at site 1.